The impact of physical exercise on neuromuscular function in Myasthenia gravis patients: A single-subject design study - Westerberg, Elisabet (Medicine (Baltimore), 2018)
There is a need for tailored exercise recommendations to patients with Myasthenia gravis (MG). A few pilot studies have recently shown that physical exercise in accordance with general recommendations to healthy adults can be applied safely to patients with mild MG symptoms. How physical exercise affects muscle parameters and risk factors for lifestyle diseases in patients with MG is, however, only poorly known. We evaluated functional skeletal muscle parameters in 11 MG patients, before and after conducting a 12-week supervised physical therapy regimen of aerobic and resistance strength training. After the training program, parameters of the rectus femoris muscle improved: compound motor action potential (from 4.5 ± 2.6 to 5.3 ± 2.8 mV, P = .016), isometric muscle force (from 25.2 ± 4.4 to 30.2 ± 3.8 kg; P = .014), and ultrasound muscle thickness (from 19.6 ± 5.6 to 23.0 ± 3.9 mm, P = .0098) all increased. Further, physical performance based measures improved, including the 30-Second Chair Stand Test (median change +2, P = .0039) as well as the clinical MG composite score [from 3 (2–5) to 2 (0–4), P = .043]. No improvement in muscle function was observed in the biceps brachii muscle. These findings indicate that MG patients can improve their muscular functions by incorporating aerobic and resistance strength training, especially in proximal leg muscles. This is important knowledge when physical therapy is considered for this patient group, for whom no guidelines on physical exercise currently exist.